1995
DOI: 10.1105/tpc.7.11.1823
|View full text |Cite
|
Sign up to set email alerts
|

The large-scale genomic organization of repetitive DNA families at the telomeres of rye chromosomes.

Abstract: Repetitive DNA sequences in the terminal heterochromatin of rye (Secale cereale) chromosomes have consequences for the structural and functional organization of chromosomes. The large-scale genomic organization of these regions was studied using the telomeric repeat from Arabidopsis and clones of three nonhomologous, tandemly repeated, subtelomeric DNA families with complex but contrasting higher order structural organizations. Polymerase chain reaction analysis with a single primer showed a fraction of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
161
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(163 citation statements)
references
References 35 publications
1
161
1
Order By: Relevance
“…The sequence has 13 major subtelomeric sites and 10 minor sites in the haploid complement of this inbred line. pSc250 is a 476-bp insert in pUC18 and is a representative of a family of tandemly organized subtelomeric DNA sequences of rye with an unusually extended monomer length of $500 bp (Vershinin et al 1995). The sequence localizes to 13-14 major subtelomeric sites and six minor sites and is proximal to pSc200.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence has 13 major subtelomeric sites and 10 minor sites in the haploid complement of this inbred line. pSc250 is a 476-bp insert in pUC18 and is a representative of a family of tandemly organized subtelomeric DNA sequences of rye with an unusually extended monomer length of $500 bp (Vershinin et al 1995). The sequence localizes to 13-14 major subtelomeric sites and six minor sites and is proximal to pSc200.…”
Section: Methodsmentioning
confidence: 99%
“…Anthers were digested in an enzyme mixture comprising 0.3% (w/v) cellulase (Onozuka RS), 0.3% (w/v) pectolyase Y-23 (Seishin Pharmaceutical), and 0.3% cytohelicase (Sigma, St. Louis) in 10 mm citrate buffer (pH 4.5). pSc200 is a 521-bp insert in pUC18 comprising a 380-bp tandem repeat unit of subtelomeric DNA from rye (Vershinin et al 1995). The insert was amplified and labeled by PCR as described in Mikhailova et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…A two-monomer (2-mer) HOR has been reported for scallop PmPst9 satDNA (Biscotti et al, 2007), the plant rye has a highly abundant subtelomeric satellite sequence that is organized as a 3-mer HOR, where monomers are defined by HaeIII restriction sites and 3-mer HOR by TaqI sites (Vershinin et al, 1995), whereas centromeric repeats consisting of six monomers have been reported in rice (Lee et al, 2006). In humans, the a-satellite DNA comprises 171 bp monomers organized in a tandem, head-to-tail orientation, that can be arranged as several chromosome-specific HORs, such as the 6-mer HOR of chromosome 7 (Waye et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…1h). The sequence pSc250, amplified by PCR using total rye genomic DNA as a template to label rye heterochromatin knob DNA 22 , and the telomeric sequence were used for ISH on S. cereale cv. Petkus.…”
Section: Anticipated Resultsmentioning
confidence: 99%